Between the Visible and the Invisible. Issue 1 (24th July 2019) - Fatehrad, Azadeh
'Between the Visible and the Invisible' is based on a constellation of some of the most thought-provoking contemporary works developed through artistic research, inquiring into collective notions of memory, time and space – a moment when nothing is certain, concrete or stable; and how artistic practice could capture this sense of being 'in-between'. The paper refers to Fatehrad's recent curatorial project (Sharjah, UAE 2018) with the same title organised around three themes: disappearance, suspension and becoming. 'Disappearance' focuses on the ephemerality of recorded memory via sound or image; 'suspension' expresses a presence that is invisible yet substantive, thinkable through feelings; and 'becoming' concerns the mediation between bodily drawings and the cohabitation in holding a certain space through limited time. The concepts of diaspora and politics of location together offer a conceptual framework for a historicised analysis of contemporary (trans)national movements of people, information, culture, artistic practices, commodities and capital. 'Between the Visible and the Invisible' reflects on a rupture in time that is the exposure to a new mode of temporality based upon the continual mutability of all form. Referencing the context of 'plasticity' by Catherine Malabou (2010), this paper explores new modes of temporality through a series of multimedia installations, in particular, (i) the Psychoréographies – a performative inquiry for inner and outer spaces (15', 2015) by Nikolaus Gansterer and (ii) Anubumin (18', 2017) by Oliver Ressler, to expand on the notion of speculation within contemporary art and spatial politics.